The hepatitis B virus post-transcriptional regulatory element contains two conserved RNA stem-loops which are required for function. - Smith, G J (1998)
Human Hepatitis B Virus (HBV) RNAs contain a cis -acting sequence, the post-transcriptional regulatory element (HPRE), which facilitates the cytoplasmic localization of intronless transcripts. Our previous studies have shown that the HPRE is composed of at least two independent sub-elements, HPREalpha and HPREbeta, which co-activate a reporter for RNA export in a greater than additive manner. Utilizing deletion, mutation and co-variational analyses, we have identified three regions important for full HPRE activity. The three separate regions of the HPRE function can function independently in a dose-dependent manner when multimerized. Two of these regions contain stem loops, HSLalpha and HSLbeta1, which are necessary for full HPRE function. These structures are conserved throughout the mammalian Hepadnaviruses. Disruption of either stem-loop structure by mutagenesis decreases HPRE function while compensatory mutations restore activity. The location of the stem-loops in the genome reveal that they are present in all of the HBV transcripts. HSLalpha and HSLbeta1 are likely to contain the binding sites for the cellular factor(s) which mediates HPRE function.